Goal adjustment by people living with long-term conditions: A scoping review of literature published from January 2007 to June 2018. Issue 8 (14th September 2021) - Scobbie, Lesley; Thomson, Katie; Pollock, Alex; Evans, Jonathan
ABSTRACT: Long-term health conditions can limit achievement of personal goals. We aimed to map and synthesize definitions of goal adjustment, theoretical underpinnings, associations with recovery and supportive interventions for adults with long-term conditions. We searched multiple databases (January 2007–June 2018) and identified peer-reviewed research relating to goal adjustment. Data were charted, mapped and synthesized using content analysis and descriptive summaries. Two stakeholder consultations informed the review. Ninety-one articles were included. A range of long-term conditions were represented including cancer (22%), stroke (12%) and mixed neurological conditions (8%). Goal adjustment was one available option when faced with unattainable goals; other options were goal disengagement and goal re-engagement. Most studies were quantitative (58%), reporting mainly positive associations between goal adjustment, disengagement, reengagement and recovery. The Dual Process Model, Goal Adjustment Model and Self-Regulation Theory were most cited underpinning models/theory. Five interventions were identified; only one (self-system therapy) was evaluated in a randomized controlled trial. Our review provides original and significant insights into goal adjustment definitions, theoretical underpinnings and association with recovery. Effective interventions to support goal adjustment, disengagement and reengagement are lacking. This research-practice gap warrants attention to ensure people with long-term conditions are optimally supported when facing unattainable goals.